Exploring the crisis management strategies of teams in the national Lacrosse League during the COVID-19 pandemic. - Wolkowski, J. T. (University of Saskatchewan, 2021)
The world has gone through many crises, including devasting pandemics, in the past. At present, the world continues grappling with the COVID-19 (SARS-COV-2) pandemic. In the first year of the pandemic, nations chose to go into lockdowns to reduce the severity of the crisis, using actions that included staying-at-home orders and business closures. An industry that was forced to close was the professional sports industry. On March 11th, 2020, the National Basketball Association announced that their league was temporarily stopping play because of the pandemic, with many other leagues following suit. After establishing safety protocols to keep teams (and fans) safe, top-tier professional sports leagues restarted during the pandemic. However, second-tier leagues struggled in finding a way to restart or begin their seasons, while some of these second-tier leagues had to cancel their season entirely. The purpose of this thesis is to explore the actions and strategies that professional sports teams and leagues have been taking through the COVID-19 crisis. The literature review provides insights into crisis management strategy as it has been studied across many fields, including professional sports. Turning to one of the most studied perspectives, a three-phase crisis management strategy provides the platform for evaluating the pre-crisis, during-crisis, and post-crisis actions taken in professional sports. The pre-crisis phase is focused on planning on what to do for potential crises. During a crisis, organizations pick the strategies created in the pre-crisis phase that would best limit the damage from the crisis that they currently face. Finally, the post-crisis phase focuses on learning from the strategies implemented, taking feedback and redesigning strategies for future crises. Case study methods were used for this research, using seven semi-structured interviews and press releases, websites, and social media content to gather and interpret data. The findings tell the story of how four teams, along with the league headquarters of the National Lacrosse League (NLL), handled themselves during the pandemic, a time of great uncertainty for everyone. Analysis of transcripts included identifying the frequency that actions were taken that matched the best practices advice from the literature on the three-phase crisis management strategy. It was revealing, with ample indications, that teams and the league had little of the pre-crisis underlayment recommended by the literature. These actions meant that there was little anticipation of, nor preparation for, significant scale crises. When the pandemic struck, there was nothing "in the books" to turn to by the NLL, i.e., no game plan for crises. However, there were many strategies utilized. For example, there was much communication that allowed for the best strategies to be created. Because the COVID-19 pandemic is still happening, there is not much information on the post-crisis phase of the NLL, although the interviewees provided many forward-looking observations.